Rotura espontánea de tumor ovárico con complicaciones - Tong Zhao, MD (2026)
Mucinous ovarian adenocarcinoma is rare among malignant neoplasms of thefemale reproductive tract and is common in child-bearing period women. Patients often have non-specific symptoms, and diagnosis is usually based on histopathologic findings due to the lack of specific preoperative diagnostic elements , spontaneousrupture of ovarian cysts leads to more difficult diagnosis for emergent cases, and our patient complicated by stress-induced gastrointestinal bleeding intraoperatively, which added complexity to the surgery, We hope that the publication of the present case will increase awareness of the management of ruptured ovarian tumor among physicians and prevention of stress-induced gastrointestinal bleeding.